STUDY OF ISOLATE MOUND GROUP №6 IN THE SOUTHERN AREA OF THE PALASA-SYRT BURIAL GROUND OF THE IV-V CENTURY - Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2015)
The author of the article analyzes new materials from the Palasa-Syrt burial mound of the 4th-5th cc., obtained in 2015 during the excavations of mound group No.6, which included seven mounds.The funeral rites of this group had traditional features. The burials were made in catacombs, and the chambers were located perpendicular to the entrance pit. Under each burial mound was one, except for the mound in 1573, which had two graves –of an adult woman and a 7-8 month-old child. All the burials, except for the child’s, were ransacked in ancient times, but among the preserved grave goods there are unique articles of woman’s dress (mound 1577); a rich child’s necklace (mound 1573, burial 2); bronze clasps (mounds 1569, 1572); a jug with zoomorphic handle (mound 1577). The burials date back to the first quarter of the 5th century.
Keywords: Palasa-Syrt burial mound; mound group №6; funeral rites; catacombs; grave goods